2001
DOI: 10.1046/j.1365-2222.2001.01064.x
|View full text |Cite
|
Sign up to set email alerts
|

Diet and chronic obstructive pulmonary disease: independent beneficial effects of fruits, whole grains, and alcohol (the MORGEN study)

Abstract: Our results suggest independent beneficial effects of fruits, whole grains and alcohol on COPD that are largely additive and cannot be explained by smoking habits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
123
3
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 131 publications
(144 citation statements)
references
References 37 publications
12
123
3
2
Order By: Relevance
“…Still, the results suggest a protective effect of a high intake of fruit against COPD. This is in agreement with the results of most cross-sectional studies Tabak et al, 1999Tabak et al, , 2001aButland et al, 2000) and with the results of two of the three longitudinal studies (Butland et al, 2000;Miedema et al, 1993;Carey et al, 1998). Miedema et al (1993) observed an inverse relation between baseline consumption of total and especially solid fruit ( ¼ apples, pears) and 25 y chronic lung disease incidence in the Dutch cohort of the Seven Countries Study.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Still, the results suggest a protective effect of a high intake of fruit against COPD. This is in agreement with the results of most cross-sectional studies Tabak et al, 1999Tabak et al, , 2001aButland et al, 2000) and with the results of two of the three longitudinal studies (Butland et al, 2000;Miedema et al, 1993;Carey et al, 1998). Miedema et al (1993) observed an inverse relation between baseline consumption of total and especially solid fruit ( ¼ apples, pears) and 25 y chronic lung disease incidence in the Dutch cohort of the Seven Countries Study.…”
Section: Discussionsupporting
confidence: 89%
“…Butland et al (2000) reported a nonsignificant trend towards an inverse relation between baseline apple consumption and change in FEV 1 . As has been observed earlier (Tabak et al, 2001a) the effect of fruit intake appeared to be largely independent of that of alcohol consumption. In none of the longitudinal studies that investigated vitamin C intake in relation to indicators of COPD (including our own) a clear association was observed (Miedema et al, 1993;Butland et al, 2000).…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Higher levels of dietary or plasma antioxidants have been associated with better pulmonary function, as demonstrated by a higher level and lower rate of decline of the forced expiratory volume in 1 s (FEV 1 ), and a decreased risk of chronic obstructive pulmonary disease (COPD) [35,36]. Major nonenzymatic antioxidants present at respiratory tract surfaces include ascorbate, urate, α-tocopherol, reduced glutathione (GSH), mucins, and albumin.…”
Section: Oxidative Stress In the Lungmentioning
confidence: 99%